FATIMAH MERNISSI PEREMPUAN BERPELUANG SEBAGAI KEPALA NEGARA - Jamhari Jamhari (Jurnal Studi Agama, 2018)
Mernissi has tried to dismantle the building of interpretations of classical scholars, She tried to dismantle injustice feminism through criticism of the hadith about women's leadership, which according to her must be examined again in terms of asbab al-nuzul and historically why hadith or verse came down. As a sociologist, Mernissi did not only approach textual texts in conducting her studies. However, religious texts must be studied from a historical-sociological approach. This is to find the significance of meaning, if it is related to the conditions of the times and places. The hermeneutic approach, used by Mernissi, is to criticize the verses of the Qur'an and misogyny hadiths. She reveals the historical background to the following hadiths had misogyny about the quality of the narrators to find the true meaning of the text. Related to women being head of state according to Mernissi in essence, and what is a problem according to Mernissi is not the problem of men and women but how they are able to become leaders themselves.